Predictors of futile recanalisation in patients with large infarct: a post-hoc analysis of the ANGEL-ASPECT trial - Zhongrong Miao; Xiaochuan Huo; Wenhuo Chen; Yuesong Pan; Mengxing Wang; Tingyu Yi; Xiufen Zheng; Yan-min Wu; Ding-lai Lin; Xiaohui Lin; Zhinan Pan (Stroke and Vascular Neurology)
Background Studies on futile recanalisation after endovascular therapy (EVT) for anterior circulation large vessel occlusion with large infarct were scarce. The present study aimed to explore the incidence and independent predictors of futile recanalisation in patients with large infarct.Methods This is a post-hoc analysis of the ANGEL-Alberta Stroke Program Early CT (ASPECT) trial. A favourable outcome was defined as a 90-day modified Rankin Scale score of 0−3; successful reperfusion was defined as extended thrombolysis in cerebral infarction 2b, 2c and 3 on final angiogram; and futile recanalisation was defined as unfavourable outcome despite successful reperfusion. We performed multivariate analysis to identify the predictors of futile recanalisation after EVT in patients with large infarct.Results A total of 183 patients were included: 91 (49.7%) patients had futile recanalisation and 92 (51.3%) had meaningful recanalisation. In multivariable logistic regression analysis, nonmodifiable factors included older age (age ≥68 years, OR=3.4, 95%CI 1.5 to 7.7, p= 0.003), female sex (OR=2.78, 95%CI 1.28 to 7.27, p=0.01), higher National Institutes of Health Stroke Scale score (NIHSS ≥16, OR=3.1, 95%CI 1.2 to 8.3, p=0.035), diabetes (OR=3.1, 95%CI 1.2 to 8.3, p=0.017) and symptomatic intracranial haemorrhage (sICH) (OR=9.1, 95%CI 1.0 to 80.7, p=0.049), and modifiable factors included larger final infarct volume (FIV ≥174.7, OR=6.2, 95%CI 2.5 to 15.7, p<0.001) and postoperative respiratory failure (OR=14.1, 95%CI 1.6 to 124.8, p=0.018), which were independent predictors of futile recanalisation.Conclusions Futile recanalisation occurred in approximately half of patients who had an acute stroke with large infarct after EVT in the ANGEL-ASPECT trial. Nonmodifiable factors that included old age, high baseline NIHSS score, diabetes mellitus, sICH and large FIV, and modifiable factors that included respiratory failure were independent predictors of futile recanalisation after EVT for large ischaemic strokes. Stroke-related pneumonia control may improve prognosis.